Understanding Stress and its Management in Unani Medicine: A Psychoneuroimmunological and Pharmacological Review - Mohd Suheb; Mohammad Shahid; Mohd Zubair; Zaki Siddiqui (International Journal For Multidisciplinary Research, 2026)
Stress-related disorders, including generalized anxiety disorder, clinical depression, and psychosomatic illnesses, constitute a substantial and growing component of the global burden of disease and account for approximately 12–15% of mental health consultations worldwide.¹ Although modern medicine commonly employs target-specific psychopharmacological agents, such as selective serotonin reuptake inhibitors (SSRIs) and benzodiazepines, their clinical use may be associated with adverse effects, including gastrointestinal disturbances, weight gain, metabolic alterations, and cognitive or motor impairment.² This review examines stress from the perspective of Unani (Greco-Arab) medicine, with particular emphasis on its classical theoretical framework, historical contributions to psychiatric medicine, and contemporary pharmacological evidence. In Unani Tibb, stress-related psychological disorders are considered within the broader category of Amraz-e-Nafsaniya. The Unani approach conceptualizes psychological distress in relation to disturbances of Mizaj (temperament) and Akhlat (humours), particularly alterations associated with Safra (yellow bile) and Sauda (black bile). These disturbances are traditionally considered to influence the temperament and functioning of Ruh (vital spirit) and Qalb (heart), thereby affecting the regulatory capacity of Tabiyat.⁶ Unani medicine offers a multidimensional approach to the management of stress through the regulation of Asbab-e-Sitta Zarooriya (the six essential causes), Ilaj-bil-Tadbeer (regimental therapy), and Ilaj-bil-Dawa (pharmacotherapy). Regimental approaches include interventions such as Dalk-e-Layyin (gentle massage), while several medicinal plants traditionally used in Unani medicine have also been investigated for their potential adaptogenic, anxiolytic, and neuroprotective effects.⁸,¹² Among these, Withania somnifera (Asgand), Nardostachys jatamansi (Jatamansi), and Bacopa monnieri (Brahmi) have received particular scientific attention. Available experimental and clinical evidence suggests that these botanicals may influence the hypothalamic–pituitary–adrenal (HPA) axis, modulate stress-related neuroendocrine responses, and influence oxidative and inflammatory pathways.³ This review therefore explores the potential role of Unani principles and interventions in stress management while examining their possible correlations with contemporary concepts of psychoneuroimmunology.